2020
DOI: 10.1097/gme.0000000000001525
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes associated with menopause among women aged 45 to 60 years: a pilot study among rural and urban women in Bangladesh

Abstract: Objective: To assess knowledge and attitudes associated with the menopause transition among women in Bangladesh. Methods: A cross-sectional survey was conducted among women (age range 45-60 y), 160 participants were selected from both urban and rural settings using a systematic sampling procedure. We used face-to-face interview techniques employing a semistructured questionnaire. Bivariate and multivariate regression analyses were done to assess the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…Interestingly, the attitude toward menopause was highly positive (340, 58%), which suggests women might be willing to know more about menopause and its related symptoms. These results align with other countries in the region that showed poor to fair knowledge on this subject 14,15 . We can relate this poor knowledge to the generally conservative nature of the UAE and the Eastern community.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, the attitude toward menopause was highly positive (340, 58%), which suggests women might be willing to know more about menopause and its related symptoms. These results align with other countries in the region that showed poor to fair knowledge on this subject 14,15 . We can relate this poor knowledge to the generally conservative nature of the UAE and the Eastern community.…”
Section: Discussionsupporting
confidence: 87%
“…Postmenopausal status, older age and high cultural level were associated with a greater likelihood of knowing the health benefits of a healthy lifestyle. Indeed, the culture and lifestyle habits of each country could have an impact on women's beliefs and the importance assigned to such habits when it comes to experiencing a healthy menopause [10,28,29]. Perhaps the strongest proponents of the link between lifestyle factors and menopause are Asian women.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, the Women’s EMPOWER survey, an internet-based survey of US women with VVA symptoms [ 4 ], reported that most women were aware of over-the-counter treatments (vaginal lubricants or moisturizers) but knew rather less about options such as local estrogen treatments. Other surveys evaluated the knowledge, behavior, and attitudes associated with GSM; the authors valued treatments women receive, their satisfaction and concerns, but the treatment options that women are aware of are not discussed in depth [ 9 , 10 , 15 17 ]. This is an important aspect to consider if patients are to choose the most appropriate treatment according to their preferences.…”
Section: Discussionmentioning
confidence: 99%